The Intersection of Political Identity and Tools of Victory in The Upcoming Electoral Contest - Octo Iskandar (Siber International Journal of Advanced Law (SIJAL), 2024)
The 2024 elections in Indonesia will mark a historic moment as the first simultaneous election to determine members of the legislature, president, vice president, regional heads, and deputy regional heads, even though they will be conducted on different dates and months. This democratic event will take place amid a strong surge in public participation, characterized by various sociopolitical phenomena expressed through diverse ideas and behaviors. Such phenomena have been evident in previous elections, including the 2019 elections, and others before and after, addressing issues such as the politicization of religion, race, ethnicity, and other non-electoral issues. This study aims to identify non-electoral factors that may emerge before and/or during the 2024 elections, potentially triggering electoral conflicts. The research utilizes a qualitative approach with data collection through literature review and analysis of sociopolitical phenomena related to elections. Hypothetically, the study's results suggest that several non-electoral factors (social, political, cultural, religious, economic, and legal) have the potential to escalate and intensify conflicts during the 2024 elections, ultimately disrupting the electoral process and/or casting doubt on the legitimacy of the results.